2014
DOI: 10.1002/hep.26898
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor inhibition attenuates liver fibrosis and development of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most rapidly increasing cause of cancer-related mortality in the United States. Because of the lack of viable treatment options for HCC, prevention in high risk patients has been proposed as an alternative strategy. The main risk factor for HCC is cirrhosis and several lines of evidence implicate epidermal growth factor (EGF) in the progression of cirrhosis and development of HCC. We therefore examined the effects of the EGF receptor (EGFR) inhibitor erlotinib on liver fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
295
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 309 publications
(319 citation statements)
references
References 37 publications
12
295
2
3
Order By: Relevance
“…The antifibrotic effects of EGFR inhibition have been reported in several experimental models of chronic diseases, including renal fibrosis. 13,[17][18][19][20] However, the potential of EGFR inhibitors to act as therapeutic agents to ameliorate peritoneal membrane damage has not been studied yet. In this study, we showed that early or late administration of gefitinib, an EGFR inhibitor, reduced deposition of ECM with inactivation of myofibroblasts, suppression of inflammation responses, and attenuation of angiogenesis in the injured peritoneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifibrotic effects of EGFR inhibition have been reported in several experimental models of chronic diseases, including renal fibrosis. 13,[17][18][19][20] However, the potential of EGFR inhibitors to act as therapeutic agents to ameliorate peritoneal membrane damage has not been studied yet. In this study, we showed that early or late administration of gefitinib, an EGFR inhibitor, reduced deposition of ECM with inactivation of myofibroblasts, suppression of inflammation responses, and attenuation of angiogenesis in the injured peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…15 STAT3 can also regulate expression of ECM proteins, such as type 1 collagen, and plays an important role in mediating the differentiation of renal interstitial fibroblasts to myofibroblasts and the development of renal fibrosis. 16 EGFR has been linked to tissue fibrosis in a variety of organs, including the liver, 17 lung, 18 and kidney. 13,19,20 However, it is unknown whether EGFR is activated in the peritoneum or whether it is involved in peritoneal fibrosis after injury.…”
mentioning
confidence: 99%
“…Notably, a recent study confirms that the superstructure of galectins at the cell surface can bind cell-surface receptors such as epidermal growth factor receptor, which is a potent mitogen for collagen-producing mesenchymal cells (Partridge et al, 2004;Martinelli et al, 2011;Fuchs et al, 2014). Besides, Gal-3 exhibits high-affinity binding for the advanced glycosylation end product-binding proteins in macrophages, astrocytes, and endothelial cells.…”
Section: Cell Receptors and Ligandsmentioning
confidence: 82%
“…Hepatic fibrosis is considered as a wound-healing response to chronic liver injury, which may result in liver cirrhosis and HCC, thus significantly correlated with prognosis of HCC [23,24]. The extent of hepatic fibrosis has usually been evaluated by histological exanimation.…”
Section: Discussionmentioning
confidence: 99%